PERKEMBANGAN TAFSIR AL-QUR’AN PADA MASA SAHABAT - Andi Miswar (Universitas Islam Negeri Alauddin Makassar, 2016)
Interpretation of al-Qur'an have grown during Prophet life and he is the first mufassir. After Rasulullah passed away the prophet companies occupied the second interpretor. The first person interpreted al-Qur'an after Rasul is Ali and than Ibnu Abbas. Al-Qur'an was interpreted by prophet companieas by using sources such as Qur’an, prophet tradition,their own opinions (ijtihad) and israiliyat stories ( though this was not mentioned and not allowed by the Prophet.). Meanwhile interpretation of Prophet directly come from Allah or passed by jibril or from himself, difference ways of this two interpretation are not far differences, but the quality of these interpretations is far more eminent. Generally, the form of interpretation applied by prophet companies is called al-Ma'tsur interpretation which means that the interpretation is based on prophet interpretation, tradition and hisrory. This doesn’t mean the ra’yu or thought was not exluded but included. Precisely in certain condition, they used ideas called interpretation method (ijtihadi). The methode of interpretation used was ijmali ( global), which means a brief and clear interpretation of verses.